Morphological variation of Trilepida macrolepis (Peters 1857), with reappraisal of the taxonomic status of Rena affinis (Boulenger 1884) (Serpentes: Leptotyphlopidae: Epictinae) - Pinto, Roberta R.; Fernandes, Ronaldo (Zootaxa, 2017)
We report on the morphological variation (meristic, morphometric, pholidosis, and color pattern characters) and sexual dimorphism of Trilepida macrolepis. We also took the opportunity to redescribe the holotype of Rena affinis in an effort to evaluate its taxonomic status. Based on the congruence of characters from external morphology, we transfer Stenostoma affine to the genus Trilepida. We also discuss the Andean specimens previously refereed to Trilepida affinis and Trilepida macrolepis and provide an identification key for the genus Trilepida.